Antitumor activity of extracts from Peperomia elongata - de Castro Campos, Patricia Bonavides; Torres Gama, Juliana Julian [UNESP]; Pereira, Licia Pacheco; Costa-Lotufo, Leticia Veras; de Moraes, Manoel Odorico; Guimaraes, Elsie Franklin; Kato, Massuo Jorge; Furlan, Maysa [UNESP]; Pessoa, Claudia (Taylor & Francis Inc, 2007)
The cytotoxic potential of ethanol extracts from Peperomia elongata H. B. & K. (Piperaceae) were evaluated against human cancer cell lines by the MTT method. The samples considered cytotoxic were tested for antimitotic activity with the sea urchin egg development test and for hemolytic activity using mice erythrocytes. The extracts from leaves (hexane), stems (ethanol, hexane, hexane: AcOEt, AcOEt, and MeOH: H2O insoluble), and roots (R4) presented potential cytotoxic action. The stems extracts showed the highest toxicity in all tumor cell lines tested, with an IC50 <= 9.0 mu g/mL for ethanol extract, IC50 <= 11.6 mu g/mL for MeOH:H2O insoluble, IC50 <= 7.3 mu g/mL for hexane extract, IC50 <= 11.4 mu g/mL for hexane: AcOEt, and IC50 <= 16.2 mu g/mL for AcOEt extract. All extracts considered cytotoxic for tumoral cell lines presented antimitotic activity. The samples from roots (R4) and stems (ethanol, MeOH: H2O insoluble, and hexane extract from leaves) were found to possess lytic activity in mice erythrocytes but in higher doses (> 125 mu g/mL). Further studies for the isolation and identification of the active principles of these extracts should be undertaken.
Keywords: antitumor; cytotoxic activity; MTT assay; Peperomia; piperaceae